A CLASSIFICATION OF THE CUBIC SEMISYMMETRIC GRAPHS OF ORDER 34p - Alaeiyan, Mehdi; Aramian, Rasul (IndoMS, 2011)
A simple undirected graph is called semisymmetric if it is regular and edge transitive but not vertex-transitive. In this paper, we classify all connected cubic semisymmetric graph of order 34empsup2;/em, where p be a prime.DOI :Â http://dx.doi.org/10.22342/jims.17.1.9.11-15